Política e protesto no Brasil recente: uma análise das manifestações de junho de 2013 na cidade de São Paulo - Lopes, Eser Azael Moreira (2018)
The present work presents an analysis of the political dimensions of the so-called "street demonstrations of June 2013" in Brazil, having as empirical field the city of São Paulo / SP, where the acts began through protests against the increase of public transportation passes and spread throughout the country through the circulation of information via social networks. Through two distinct media (Folha de São Paulo and Ninja Media), in addition to data collected by public opinion polls, the analysis was focused on the political and ideological manifestations of these acts, taking into account the right-left dyad. From this point of view, the June protests in São Paulo had three distinct moments: they began with acts of an organized group with left ideological leanings, the Free Passage Movement (MPL); soon afterwards, reached public opinion and became widespread, spreading throughout the country, driven by the phenomenon of social networks, taking to the streets a large and heterogeneous mass of demonstrators with diverse patterns, demands and social profiles. in turn, a crossroads of ideologies in the streets of São Paulo; the different ideological profiles, because of their divergent character, motivated several conflicts, one of them occurred explicitly putting in antagonism some groups of the left and a part of demonstrators that was titled nonpartisan or antipartidária, this third and last moment ended up separating and fragmenting the acts in the city. It is understood that the protests of June indicated an ideological split that accentuated in the course of the years in the country, but that, although of an initial form, already was put in the streets during the acts of that month. When the protests became widespread and spread throughout the country, the Federal Government, led by the Workers' Party (PT), came under the banner of the protesters. It is understood that this is due to the contradictory character of government that was adopted by the party and the episodes of corruption, that entered to the critic of the public opinion. This contradictory character of the PT governments is understood here as a phenomenon of Lullism characterized by a gradual reform centered on a conservative pact. It is argued that such phenomenon is highlighted during the June acts by a large number of protesters, rejecting such a political proposal for Brazil.